2011
DOI: 10.2298/tsci100412060r
|View full text |Cite
|
Sign up to set email alerts
|

Numerical heat transfer studies of a latent heat storage system containing nano-enhanced phase change material

Abstract: The heat transfer enhancement in the latent heat thermal energy storage system through dispersion of nanoparticle is reported. The resulting nanoparticle-enhanced phase change materials (NEPCM) exhibit enhanced thermal conductivity in comparison to the base material. The effects of nanoparticle volume fraction and some other parameters such as natural convection are studied in terms of solid fraction and the shape of the solid-liquid phase front. It has been found that higher nanoparticle vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Ranjbar et al [84] investigated the effect of dispersing copper nanoparticles in water on the solid-liquid phase change interface by using an enthalpy-porosity numerical modelling method. It was concluded that the heat conduction was dominant in both solid and liquid phases.…”
Section: Numerical and Experimental Investigation On Thermodynamic Bementioning
confidence: 99%
“…Ranjbar et al [84] investigated the effect of dispersing copper nanoparticles in water on the solid-liquid phase change interface by using an enthalpy-porosity numerical modelling method. It was concluded that the heat conduction was dominant in both solid and liquid phases.…”
Section: Numerical and Experimental Investigation On Thermodynamic Bementioning
confidence: 99%
“…In addition, their numerical results showed reduction in the overall solidification time. Ranjbar et al [12] investigated the influence of utilizing nanoparticle on enhancement of heat transfer in a three-dimensional cavity. They showed that the suspended nanoparticles substantially increase the heat transfer rate.…”
Section: Journal Of Engineeringmentioning
confidence: 99%
“…To conquer this limitation, various heat transfer enhancement methods are investigated including employment PCM microencapsulation [22,23], using multiple array of PCMs [24,25], dispersing high thermal conductive materials [26,27] and using NePCMs [28,29]. Utilizing extended surfaces techniques has attracted a great amount of attention which includes fined tubes and multi-tubes.…”
Section: Introductionmentioning
confidence: 99%